2014
DOI: 10.1007/s10096-014-2266-9
|View full text |Cite
|
Sign up to set email alerts
|

Mixed infections with distinct cytomegalovirus glycoprotein B genotypes in Polish pregnant women, fetuses, and newborns

Abstract: The purpose of this investigation was to describe a distribution of cytomegalovirus (CMV) single and multiple genotypes among infected pregnant women, their fetuses, and newborns coming from Central Poland, as well as congenital cytomegaly outcome. The study involved 278 CMV-seropositive pregnant women, of whom 192 were tested for viral DNAemia. Human cytomegalovirus (HCMV) genotyping was performed for 18 of 34 pregnant women carrying the viral DNA and for 12 of their 15 offspring with confirmed HCMV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In other studies, gB-1 has been detected as the predominant genotype (46% of all infants). 24,25 Rycel et al 23 argued that the genotypic variability of CMV seems to be geographically related, because rates of mixed infections varied from low frequency (2% in Chinese) to high frequency (45% in American infants). Furthermore, despite genotypic variability of CMV seems to be geographically related, different genotypification methodologies have proven different sensitivities for mixed infection detection.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, gB-1 has been detected as the predominant genotype (46% of all infants). 24,25 Rycel et al 23 argued that the genotypic variability of CMV seems to be geographically related, because rates of mixed infections varied from low frequency (2% in Chinese) to high frequency (45% in American infants). Furthermore, despite genotypic variability of CMV seems to be geographically related, different genotypification methodologies have proven different sensitivities for mixed infection detection.…”
Section: Discussionmentioning
confidence: 99%
“…In CMV seropositive women, the risk factors for congenital infection are less well defined, although in a recent study of pregnant Polish women, around 22% of seropositive women who transmitted to their neonate were infected with multiple CMV strains as judged by glycoprotein B genotyping 20 . Additional studies by targeted sequencing demonstrated that other genes of CMV have highly variable regions including proteins gN, gO, gH, and UL144 2 , 3 .…”
Section: Cytomegalovirus In Pregnancy: Risk Factors and Epidemiologymentioning
confidence: 99%
“…On the other hand, there is evidence proposing that coinfection with more than 1 HCMV strain may be a frequent event at birth in children with congenital infection . Ross et al analyzed samples of saliva, urine, and blood from 28 children with HCMV congenital infection using PCR, followed by cloning and Sanger sequencing for the gN, gB, and gH genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies in low HCMV seroprevalence populations showing the occurrence of multiple HCMV strains in the urine, saliva, and blood of children with congenital infection by this virus, there are no studies in populations with high seroprevalence . It is not known whether women with nonprimary infection, even if they are carriers of more than 1 viral strain, transmit 1 or more strains with which they had contact during or before gestation.…”
Section: Introductionmentioning
confidence: 99%